2017
DOI: 10.1186/s13293-016-0122-6
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor overexpression in mice abrogates sex differences in body weight, visceral fat, and food intake response to a fast and alters levels of feeding regulatory hormones

Abstract: BackgroundCorticotropin-releasing factor overexpressing (CRF-OE) male mice showed an inhibited feeding response to a fast, and lower plasma acyl ghrelin and Fos expression in the arcuate nucleus compared to wild-type (WT) mice. We investigated whether hormones and hypothalamic feeding signals are impaired in CRF-OE mice and the influence of sex.MethodsMale and female CRF-OE mice and WT littermates (4–6 months old) fed ad libitum or overnight fasted were assessed for body, adrenal glands and perigonadal fat wei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 78 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Here, upregulated PVN CRH mRNA in response to RRS for both male and female TCRβ−/−δ−/− mice demonstrates another example of loss of sex-differences in Immunocompromised mice. Previous studies exploring CRH overexpressing mice have found corresponding losses of sexual dimorphism (Wang et al, 2017). In addition, forthcoming work in our lab that has identified losses of sexual dimorphism in microglia number in stress-mediating brain regions (Thompson et al, in preparation).…”
Section: Discussionmentioning
confidence: 79%
“…Here, upregulated PVN CRH mRNA in response to RRS for both male and female TCRβ−/−δ−/− mice demonstrates another example of loss of sex-differences in Immunocompromised mice. Previous studies exploring CRH overexpressing mice have found corresponding losses of sexual dimorphism (Wang et al, 2017). In addition, forthcoming work in our lab that has identified losses of sexual dimorphism in microglia number in stress-mediating brain regions (Thompson et al, in preparation).…”
Section: Discussionmentioning
confidence: 79%
“…The observation of the dramatic differences in arcuate nucleus neuropeptide expression between sexes is novel and was initially surprising to us. This has not, as far as we know, been previously investigated or observed in birds and little researched even in mammals [ 41 43 ]. In our experiments, both AGRP and NPY expression were significantly higher in males than females.…”
Section: Discussionmentioning
confidence: 96%
“…Leptin is reported to increase rapidly on a HFD, then decrease, only to rise again with an increased fat mass . Males had higher leptin levels than females, indicating that this sex difference found in adult mice and rats can also be seen during the peripubertal period.…”
Section: Discussionmentioning
confidence: 99%